Cleft lip and palate based on birth order and family history at Mitra Sejati General Hospital, Indonesia - Hendry Rusdy; Isnandar; Indra Basar Siregar; Veronica (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2022)
Background: Cleft lip and palate is one of the most common congenital abnormalities in infants and is caused by more than one factors, which can be genetic and environmental. Defects in a family gene can result in cleft lip and palate. The study found a high family history relationship with the incidence of cleft lip and palate. Birth order studied by several researchers also has different results, which were influenced by folic acid consumption, maternal knowledge, lack of antenatal care visits and maternal age. To determine the cases of cleft lip and palate based on the birth order of the children and family history of the patients at Mitra Sejati General Hospital. Purpose: The study aimed to investigate cleft lip and cleft palate patients by birth order and family history. Methods: This research was a retrospective descriptive study using survey method. Researchers gave 13 questions through a questionnaire and data were collected and counted manually. Results: The results showed that based on the birth, the cleft case in the first birth order amounted to 25 people, the second 30 people, the third 19 people, and the fourth or more as many as 20 people. Based on family history, 27 patients had a family history of cleft lip and palate, while 67 patients did not have family history. Conclusion: The cases of clefts at Mitra Sejati General Hospital happened more frequently in the second child and most incidence did not have family history.